Characterization of a Y‐specific duplication/insertion of the anti‐Mullerian hormone type II receptor gene based on a chromosome‐scale genome assembly of yellow perch, Perca flavescens. (27th January 2020) - Feron, Romain; Zahm, Margot; Cabau, Cédric; Klopp, Christophe; Roques, Céline; Bouchez, Olivier; Eché, Camille; Valière, Sophie; Donnadieu, Cécile; Haffray, Pierrick; Bestin, Anastasia; Morvezen, Romain; et al.
Abstract: Yellow perch, Perca flavescens, is an ecologically and economically important species native to a large portion of the northern United States and southern Canada and is also a promising candidate species for aquaculture. However, no yellow perch reference genome has been available to facilitate improvements in both fisheries and aquaculture management practices. By combining Oxford Nanopore Technologies long‐reads, 10X Genomics Illumina short linked reads and a chromosome contact map produced with Hi‐C, we generated a high‐continuity chromosome‐scale yellow perch genome assembly of 877.4 Mb. It contains, in agreement with the known diploid chromosome yellow perch count, 24 chromosome‐size scaffolds covering 98.8% of the complete assembly (N50 = 37.4 Mb, L50 = 11). We also provide a first characterization of the yellow perch sex determination locus that contains a male‐specific duplicate of the anti‐Mullerian hormone type II receptor gene ( amhr2by ) inserted at the proximal end of the Y chromosome (chromosome 9). Using this sex‐specific information, we developed a simple PCR genotyping assay which accurately differentiates XY genetic males ( amhr2by + ) from XX genetic females ( amhr2by − ). Our high‐quality genome assembly is an important genomic resource for future studies on yellow perch ecology, toxicology, fisheries and aquaculture research. In addition, characterization of the amhr2by gene as a candidate sex‐determining gene in yellow perch provides a new example of the recurrent implication of the transforming growth factor beta pathway in fish sex determination, and highlights gene duplication as an important genomic mechanism for the emergence of new master sex determination genes.